DEVELOPMENT OF AN INTEGRATED SCIENCE MODULE BASED ON ETHNOSCIENCE WITH THE THEME OF VIBRATIONS, WAVES AND SOUNDS IN EVERYDAY LIFE OF CLASS VIII SMP / MTS - azizah, nikmatul; Diliarosta, Skunda (Universe, 2021)
The world of education emphasizes a learning approach so that students are able to develop their potential, collaborate with the environment, link learning with everyday life and school facilitates students to be involved in their social environment. A suitable scientific approach is learning based on local wisdom or ethnoscience. based on field observations, the students' lack of interest in science learning was due to the learning material in textbooks still monotonous. To overcome this problem, researchers developed a science module based on ethnoscience or local wisdom of West Sumatra, which is easy for junior high school students to understand so that it can increase interest in learning. The purpose of this research is to produce a science module based on the ethnoscience of vibrations, waves and sounds. then tested its validity so that it is suitable for use in class VIII science learning. The type of research used is research and development (R&D). the development model used is ADDIE. The research instrument used was a validity questionnaire. The research data were analyzed using descriptive statistics. This module was validated by 3 validators. The results of the validity test of each validator found that the natural science teaching materials were valid for research. Based on the research that has been done, ethnoscience-based science modules can be used with a very valid category